A global study of the unmet need for glycemic control and predictor factors among patients with type 2 diabetes mellitus who have achieved optimal fasting plasma glucose control on basal insulin. Issue 3 (13th October 2016) - Raccah, Denis; Chou, Engels; Colagiuri, Stephen; Gaàl, Zsolt; Lavalle, Fernando; Mkrtumyan, Ashot; Nikonova, Elena; Tentolouris, Nikolaos; Vidal, Josep; Davies, Melanie
Abstract: Background: This study used data from different sources to identify the extent of the unmet need for postprandial glycemic control in patients with type 2 diabetes mellitus (T2DM) after the initiation of basal insulin therapy in Europe, Asia Pacific, the United States, and Latin America. Methods: Different levels of evidence were used as available for each country/region, with data extracted from seven randomized controlled trials (RCTs), three clinical trial registries (CTRs), and three electronic medical record (EMR) databases. Glycemic status was categorized as "well controlled" (glycated hemoglobin [HbA1c ] at target [<7%]), "residual hyperglycemia" (fasting plasma glucose [FPG] but not HbA1c at target [FPG <7.2/7.8 mmol/L, <130/140 mg/dL, depending on country‐specific recommendations]), or "uncontrolled" (both FPG and HbA1c above target). Predictor factors were identified from the RCT data set using logistic regression analysis. Results: RCT data showed that 16.9% to 28.0%, 42.7% to 54.4%, and 16.9% to 38.1% of patients with T2DM had well‐controlled glycemia, residual hyperglycemia, and uncontrolled hyperglycemia, respectively. In CTRs, respective ranges were 21.8% to 33.6%, 31.5% to 35.6%, and 30.7% to 46.8%, and in EMR databases were 4.4% to 21.0%, 23.9% to 31.8%, and 53.6% to 63.8%. Significant predictor factors of residual hyperglycemia identified from RCT data included high baseline HbA1c (all countries/regions except Brazil), high baseline FPG (United Kingdom/Japan), longer duration of diabetes (Brazil), and female sex (Europe/Latin America). Conclusions: Irrespective of intrinsic differences between data sources, 24% to 54% of patients with T2DM globally had residual hyperglycemia with HbA1c not at target, despite achieving FPG control, indicating a significant unmet need for postprandial glycemic control.